Confounding effects of coral growth and high SST variability on skeletal Sr/Ca: Implications for coral paleothermometry - Grove, C.; Kasper, S.; Zinke, Jens; Pfeiffer, M.; Garbe-Schönberg, D.; Brummer, G. (2013)
Massive corals offer continuous records of climate locked within their skeleton, with the most commonly applied paleo-thermometer being Sr/Ca. Recently, however, problems with Sr/Ca thermometry indicate that the intrinsic variance of single-core Sr/Ca time series differs between cores. Here, we compare the Sr/Ca records and growth parameters of two Porites lutea colonies sampled from the same reef zone, 0.72 km apart, with two gridded SST datasets, ERSST and HadISST, off NE Madagascar. Specifically, we address seasonal and interannual variability as well as trend differences between records over the same 43 year period. The two gridded SST datasets showed strong seasonality and weak positive ENSO anomalies on a slow 43 year warming trend at significantly different rates. Both the coral Sr/Ca records showed the same clear seasonality and similar amplitudes in SST. However, on interannual timescales, they displayed diverging 43 year Sr/Ca trends and opposite responses to weak ENSO anomalies. Moreover, their growth response also differed as one coral showed increasing extension/calcification rates and Sr/Ca ratios (cooling) over the 43 years, while the other coral showed decreasing extension/calcification rates and Sr/Ca ratios (warming). Further, during positive ENSO events, the calcification rates of the two corals were negatively correlated, while skeletal density anomalies were opposite. Possible explanations to why these corals are so different may be related to the corals growth response to SST changes. The growth response of individual corals to increasing SST seems to be opposite, which in turn are likely related to biological factors. Consequently, coral growth responses explain much of the inter-colony Sr/Ca variability. © 2013. American Geophysical Union. All Rights Reserved.